Biochemical taxonomy of Crenicichla (Pisces: Perciformes: Cichlidae) of the Iguaçu River, Brazil - Renesto,Erasmo (2001)
Samples of Crenicichla iguassuensis and a morph from the Iguaçu River which differed from C. iguassuensis by its lips morphology were examined by isozyme starch electrophoresis technique. The analysis of 27 enzyme loci exhibited a genetic identity of 0.993 between the two morphs. No diagnostic locus was found that permitted to distinguish the two Crenicichla morphs. The data obtained in this investigation did not support the existence of two distinct species for this genus in the Iguaçu River, which suggested that the morphs stood for two polymorphic forms of Crenicichla iguassuensis.